CHEST RONTGEN FINDINGS IN CHRONIC KIDNEY DISEASE PATIENT WITH CONGESTIVE HEART FAILURE: A CASE REPORT - Evita Zevanya; Sudharmadji Sudharmadji (JURNAL WIDYA MEDIKA, 2023)
Chronic kidney disease is persistent abnormality or damage in kidney structure or function for more than 3 months. Prevalence of CKD is around 10 – 14% in general population and affects around more than 800 million individuals worldwide. Patients with CKD have higher risk of cardiovascular disease and synergistic pathological effects can speed up worsening of diseases. Radiology examination is one of the test that can be used to evaluate kidney and heart structural damage. The aim of this paper is to report chest rontgen findings in a man aged 54 years old with CKD with HF in 3 serials imaging result. Patient admitted to hospital caused by shortness of breath. Patient has history of hypertension, diabetes mellitus type 2, CKD stage V, and congestive heart failure. From physical examination, oxygen saturation was 97%, blood pressure was 154/115 mmHg, and extremity edema was found. Chest rontgen impression was bronchitis, dextra pleural effusion, and normal cardiac size. He got oxygen, Furosemide, Nicardipine, Aspirin, Irbesartan, Amlodipine, Calcium carbonate, and hemodialysis as therapies. After be hospitalized 2 days, patient’s condition was better, and therapy was continued outpatient. Chest rontgen examination result a year ago showed pulmonary edema, bilateral pleural effusion, and cardiomegaly with shortness of breath as major symptom. Chest rontgen examination result 6 months ago showed bronchopneumonia and cardiomegaly with fever, cough, nausea, and loss of appetite. In conclusion, most of CKD patients particularly in late stage have cardiovascular disease and radiology examination is important to detect and evaluate structural cardiac abnormality in CKD patients. Keyword: Chest rontgen, chronic kidney disease, congestive heart failure.